Preferred Online Learning Method during COVID-19 Pandemic: A Students’ Perspective - Alfelia Nugky Permatasari; Unan Yusmaniar Oktiawati (PAROLE: Journal of Linguistics and Education, 2021)
COVID-19 pandemic has been causing a massive disruption towards human life including interactions within education. Traditional learning activity in classes must be transformed into online learning to support physical distancing. This urge leads to tension, not only experienced by educators in general, but also by students. This paper aims to evaluate online learning done during the second half of even semester 2019/2020 and to find out the preferred online learning method from the students’ perspective. A number of Universitas Gadjah Mada students became the respondents answering closed and open questions related to the topic. The results show that students also experienced confusion during the process and preferred learning method which includes independent learning with prepared materials followed by virtual discussions and quizzes.